2008
DOI: 10.1177/230949900801600214
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Outcome of the Duracon Total Knee Arthroplasty

Abstract: The Duracon TKA had good midterm clinical results with absence of patellofemoral complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Similar to TSK-scores, the level of pain reported in the present study was low and with little variance, and thus did not contribute to explain the observed smaller PKSD. Low pain was also in line with findings in other studies [7,22]. Nor did AKL explain reduced PKSD.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Similar to TSK-scores, the level of pain reported in the present study was low and with little variance, and thus did not contribute to explain the observed smaller PKSD. Low pain was also in line with findings in other studies [7,22]. Nor did AKL explain reduced PKSD.…”
Section: Discussionsupporting
confidence: 80%
“…Although the present study did not have access to x-rays of the contralateral knees, it could still be proposed that there exists asymptomatic gonarthrosis limiting knee flexion [31]. As shown in other studies [4][5][6][7], TKA-subjects walked with smaller PKSD, although PPKF was sufficient both in the prosthetic knee and in the contralateral knee in order to descend stairs with similar knee flexion as controls. PPKF correlated across groups with PKSD and was the only factor that explained the variance in PKSD in the TKA-leg.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations